Tiger and turtle - Rumford, James, 1948- (New York : Roaring Brook Press, 2010)
When a tiger and a turtle both want a flower that has fallen to the ground, they argue over it until a fight breaks out between them.
A Junior Library Guild selection
"A Neal Porter book."
Keywords: Tiger -- Juvenile fiction; Turtles -- Juvenile fiction; Friendship -- Juvenile fiction; Flowers -- Juvenile fiction; Tigers -- Fiction; Turtles -- Fiction; Friendship -- Fiction; Flowers -- Fiction; Picture books for children